COMPARISON BETWEEN GASING AND CONVENTIONAL METHODS ON MATHEMATICS LEARNING OUTCOMES IN ELEMENTARY SCHOOL - Aziz Kurniawan; Ani Latifatunnisa (Universitas Islam Negeri Mataram, 2024)
The method of this study was a quantitative approach applying a field study with a quasi-experimental method. This research aimed to describe the comparison of the student’s achievement between gasing and conventional methods in mathematics learning outcomes at class IV of MI Ma'arif NU Banteran. The population was class IV which totalled 78 students. The sample used in this research was class IV A with 27 students as the experimental class and class IV B with 26 students as the control class. The data collection technique used is a test technique, then data analysis includes validity test, normality test, homogeneity test, Wilcoxon test, and N-Gain test. Based on the results of data analysis, it can be seen from the Wilcoxon test, it was found that differences in learning outcomes for students in the experimental class (gasing) and control class (conventional) obtained positive Ranks with a value of N 50, meaning that the entire sample experienced an increase in learning outcomes from pretest to posttest. Mean Ranks is 25,50 the Asymp. Sig. (2-taled) of 0,000. The Asymp. The sig value is less than 0.05, so it can be concluded that the hypothesis is accepted.